Union of the Comoros : Interim Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2006)
This paper presents a Joint Staff Advisory Note on the Union of the Comoros's Interim Poverty Reduction Strategy Paper (I-PRSP). The I-PRSP's macroeconomic framework is broadly in line with the government's objectives of improving opportunities and living conditions for the poor. It envisages higher real GDP growth, continued low inflation, higher social spending, and an ambitious medium-term public investment program. The full PRSP could develop the medium-term macroeconomic framework more fully, including by developing alternative scenarios for GDP growth and underlying sectoral performance.